A phase I, randomized, double‐blind, placebo‐controlled, single‐ and multiple dose escalation study evaluating the safety, pharmacokinetics and pharmacodynamics of VX‐128, a highly selective Nav1.8 inhibitor, in healthy adults - Hemme J. Hijma; Emilie M. J. vanBrummelen; Pieter S. Siebenga; Geert Jan Groeneveld (Wiley, 2022)
Abstract Selective inhibition of certain voltage‐gated sodium channels (Navs), such as Nav1.8, is of primary interest for pharmacological pain research and widely studied as a pharmacological target due to its contribution to repetitive firing, neuronal excitability, and pain chronification. VX‐128 is a highly potent and selective Nav1.8 inhibitor that was being developed as a treatment for pain. We evaluated the safety, tolerability, and pharmacokinetics of VX‐128 in healthy subjects in a single‐ and multiple‐ascending dose (MAD) first‐in‐human study. Pharmacodynamics were evaluated in the MAD part using a battery of evoked pain tests. Overall, single doses of VX‐128 up to 300 mg were well‐tolerated, although adverse effect (AE) incidence was higher in subjects receiving VX‐128 (41.7%) compared with placebo (25.0%). After multiple dosing of up to 10 days, skin rash events were observed at all dose levels (up to 100 mg once daily [q.d.]), in five of 26 (19.2%) subjects, including one subject receiving VX‐128 (100 mg q.d.) who had a serious AE of angioedema. A trend in pain tolerance were observed for cold pressor‐ and pressure pain, which was dose‐dependent for the latter. VX‐128 was rapidly absorbed (median time to maximum plasma concentration between 1 and 2 h) with a half‐life of ~80 h at 10 mg q.d., and approximately two‐fold accumulation ratio after 10 and 30 mg q.d. Although VX‐128, when given in a multiple dose fashion, resulted in early study termination due to tolerability issues, effects were observed on multiple pain tests that may support further investigation of Nav1.8 inhibitors as pain treatments.